Securities Transaction Taxes and Financial Markets - Habermeier, Karl (IMF Working Papers; Working Paper ;, 2001)
This paper argues that securities transaction taxes "throw sand" not in the wheels, but into the engine of financial markets where the transformation of latent demands into realized transactions takes place. The paper considers the impact of transaction taxes on financial markets in the context of four questions. How important is trading? What causes price volatility? How are prices formed? How valuable is the volume of transactions? The paper concludes that transaction taxes or such equivalents as capital controls can have negative effects on price discovery, volatility, and liquidity and lead to a reduction in the informational efficiency of markets.